2017
DOI: 10.17763/1943-5045-87.2.186
|View full text |Cite
|
Sign up to set email alerts
|

Reclaiming Adolescence: A Roma Youth Perspective

Abstract: In this article, the authors present data gathered in the Reclaiming Adolescence research project, which investigated the educational hardships of Roma youth by comparing their experiences with their non-Roma peers' in Belgrade, Serbia. Serious inequalities in access to secondary and tertiary education affect the life and career opportunities of Romani adolescents in Europe. Yet, despite a plethora of reports and surveys on this topic, the views of young Roma themselves remain undocumented. This article report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 4 publications
0
18
0
1
Order By: Relevance
“…The narratives of women presented in the previous analysis evidence what some literature has already denounced [4,22,37], i.e., the fact that educational institutions are often constructed as spaces largely blind to ethnic diversity. However, the analysis reveals that the gatherings are an example of how Roma women are finding ways to escape the risks provoked by reflexive modernization [10], which challenges the core community, family, and even equality principles that underpin Roma culture.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…The narratives of women presented in the previous analysis evidence what some literature has already denounced [4,22,37], i.e., the fact that educational institutions are often constructed as spaces largely blind to ethnic diversity. However, the analysis reveals that the gatherings are an example of how Roma women are finding ways to escape the risks provoked by reflexive modernization [10], which challenges the core community, family, and even equality principles that underpin Roma culture.…”
Section: Discussionmentioning
confidence: 53%
“…The communicative methodology of research, which guided the research, is a methodological approach characterised by its dialogic orientation that has been widely recognised for its transformative potential [36,37]. This methodology is a tool to "explain, understand, and interpret social situations which aims at changing society, -driven by utopian dreams of equality and justice" [28] (p. 237).…”
Section: Methodsmentioning
confidence: 99%
“…There are two interventions carried out in the community context, that is, the community, the neighborhood or the place where the Gypsy students live [42,43].…”
Section: Studies Carried Out In the Community Contextmentioning
confidence: 99%
“…with a longitudinal design (4 years), and the second study, by Bhabha et al [43], conducted a program, "Reclaiming Adolescence", using the design of youth participatory action research. The two studies carried out interventions in a community setting, and the former [42] considers the need to investigate the relationship between social networks, community, neighborhood and behavioral commitment, and in the case of [43], documents the opinions of Roma youth about their experiences with discrimination in secondary and university education, situating the youth as researchers. In accordance with their objectives, Rosario et al [42] promote behavioral commitment and school performance.…”
Section: Studies Carried Out In the Community Contextmentioning
confidence: 99%
“…The 2016 European Union Agency for Fundamental Rights survey identified that one in four Roma experienced racism and four in ten Roma felt discriminated against in the five years preceding the survey. Institutional forms of discrimination, including those manifested in education, have increasingly been a concern, with specific reference to direct and indirect roles in coproducing and reproducing discrimination in public law and policy (Bhabha, Matache, Chernoff, Fuller, & Lloyd McGarry, 2018;Matache, 2017b), reinforcing racialisation and thus impeding educational and career attainment (Bhabha et al, 2017;Center for European Policy Studies, 2017), and deepening structural societal inequalities (Kyuchukov & New, 2016;Ram, 2014).…”
mentioning
confidence: 99%